Human Cytomegalovirus TRS1 Protein Is Required for Efficient Assembly of DNA-Containing Capsids - Adamo, Joan E. (American Society for Microbiology, 2004)
The human cytomegalovirus tegument protein, pTRS1, appears to function at several discrete stages of the virus replication cycle. We previously demonstrated that pTRS1 acts during the late phase of infection to facilitate the production of infectious virions. We now have more precisely identified the late pTRS1 function by further study of a mutant virus lacking the TRS1 region, ADsubTRS1. We observed a significant reduction in the production of capsids, especially DNA-containing C-capsids, in mutant virus-infected cells. ADsubTRS1 exhibited normal cleavage of DNA concatemers, so the defect in C-capsid production must occur after DNA cleavage and before DNA is stably inserted into a capsid. Further, the normal virus-induced morphological reorganization of the nucleus did not occur after infection with the pTRS1-deficient mutant.